High-connection-strength lead-free solder paste and preparation method thereof
By combining flux composed of rosin additives, organic acid active agents, etc. with solder powder, high-connection strength lead-free solder paste is prepared, which solves the problem of easy breakage of solder paste during long-term use, achieves higher connection strength and stability, and improves the reliability of chip packaging.
Patent Information
- Application Number
- CN202510456833.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-12
- Publication Date
- 2025-06-24
AI Technical Summary
Existing lead-free solder paste is prone to solder breakage during long-term use, which cannot meet the reliability requirements of the chip in complex working environments.
High-connection strength lead-free solder paste made of 88-92 wt% solder powder and 8-12 wt% flux, which consists of rosin additives, organic acid active agents, thixotropic agents, surfactants, antioxidants and solvents, and is treated by emulsification and grinding to improve dispersion uniformity.
It significantly improves the connection strength and stability of lead-free solder paste, reduces the risk of solder joint breakage, and improves the reliability and service life of chip packaging.
Smart Images

Figure BDA0005355756970000051 
Figure BDA0005355756970000061 
Figure BDA0005355756970000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of soldering pastes, and more specifically, to a lead-free soldering paste with high connection strength and a preparation method thereof. Background Art
[0002] With the rapid development of electronic technology, chip packaging technology has also been continuously progressing. As one of the key materials for chip packaging, lead-free soldering paste has environmental protection and excellent solderability, and its performance directly affects the connection quality and reliability between the chip and the PCB, thereby affecting the application performance of the chip in fields such as electronic products and new energy vehicles; moreover, with the refined development of electronic products and the like, the thickness and size of the chip are getting smaller and smaller, and the solder joints are becoming more and more miniaturized, which also places higher and higher requirements on the soldering of lead-free soldering paste.
[0003] Currently, it has been found that during the long-term use of refined electronic products, the chip may experience functional failures, which are mainly due to the fracture of the solder at the chip pins, thereby causing the PCB to be open-circuited. This fracture may be due to the gradual reduction of the solder connection strength under the long-term action of thermal stress and mechanical stress of the lead-free soldering paste, which cannot meet the reliability requirements of the chip in a complex working environment. Especially during the frequent thermal expansion and contraction process and vibration process of the chip, the stress borne by the solder joints gradually accumulates, ultimately leading to the fracture of the solder and affecting the normal operation of the chip. Therefore, the applicant believes that the existing lead-free soldering paste applied to refined chip packaging still needs to be further improved. Summary of the Invention
[0004] In order to solve the problem that the existing soldering paste is prone to solder fracture during long-term use in refined chip packaging, the present application provides a lead-free soldering paste with high connection strength and a preparation method thereof.
[0005] In a first aspect, the present application provides a lead-free soldering paste with high connection strength, adopting the following technical solution: A lead-free soldering paste with high connection strength is made of 88 - 92 wt% solder powder and 8 - 12 wt% flux. The flux consists of 10 - 20 wt% rosin additive, 8 - 15 wt% organic acid activator, 5 - 8 wt% thixotropic agent, 3 - 6 wt% surfactant, 2 - 5 wt% antioxidant, and the balance solvent; The rosin additive consists of polymerized rosin, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol; The thixotropic agent consists of modified hydrogenated castor oil and ethylene bislauramide.
[0006] By adopting the above technical solutions, lead-free solder paste is prepared from solder powder and flux with relatively optimal weight percentages, and the obtained lead-free solder paste has good printing stability and welding strength. Among them, polymerized rosin, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol are used as rosin additives, modified hydrogenated castor oil and ethylene bislauramide are used as thixotropic agents, and a complex of organic acid activators, surfactants, antioxidants, and solvents is prepared. The obtained flux can effectively remove the oxide film and contaminants on the PCB board and chip pins, improve the fluidity and wettability of the prepared lead-free solder paste while enhancing the adhesion retention and thermal slump properties, thereby enhancing the connection strength and stability of the welded solder joints. It can be applied to fine chip packaging, and in complex working environments, especially during the frequent thermal expansion and contraction process and frequent vibration process of the chip, problems such as wetting and fracture of the welded solder joints are not likely to occur.
[0007] Preferably, the rosin additive is composed of polymerized rosin, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol in a weight ratio of 3:(1 - 2):(0.2 - 0.5).
[0008] By adopting the above technical solutions, using polymerized rosin, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol with relatively optimal ratios as rosin additives has good synergistic effects, can significantly improve the antioxidant performance and adhesion of the lead-free solder paste. It can uniformly wet the PCB board and chip pins, enhance the interfacial bonding force, enable the solder joints to maintain a high connection strength under long-term thermal stress and mechanical stress conditions, and form a uniform antioxidant film to prevent re-oxidation of the welding part, effectively reducing the risk of solder joint fracture, thereby improving the reliability and service life of chip packaging.
[0009] Preferably, the polymerized rosin is composed of polymerized rosin 115, polymerized rosin 140, and dimerized rosin in a weight ratio of 1:(1 - 2):(0.3 - 0.6).
[0010] By adopting the above technical solutions, using polymerized rosin 115, polymerized rosin 140, and dimerized rosin with relatively optimal ratios as polymerized rosin, the three have good synergistic effects, can have good softening point and fluidity while having good adhesion, effectively reduce the stress concentration problem of the welded solder joints during the welding process, thereby enhancing the connection strength of the welded solder joints under long-term thermal stress and mechanical stress, and reducing the fracture problem.
[0011] Preferably, the thixotropic agent is composed of modified hydrogenated castor oil and ethylene bislauramide in a weight ratio of (3 - 4):1.
[0012] By adopting the above technical solution, using modified hydrogenated castor oil and ethylene bislauramide with an optimal weight ratio as thixotropic agents can improve the shape retention ability of lead-free solder paste during the printing process, reduce the occurrence of collapse, thereby ensuring the consistency and accuracy of solder joints, forming a more stable solder joint structure during the soldering process, and enhancing the mechanical strength of solder joints.
[0013] Preferably, the modified hydrogenated castor oil is prepared by the following steps: By weight, add 40 - 60 parts of hydrogenated castor oil and 5 - 10 parts of maleic anhydride into a reaction device, heat up to 90 - 100 °C, react for 2 - 3 h after melting, then add 2 - 4 parts of cyclohexane-1,2-dicarboxylic acid diglycidyl ester and 5 - 8 parts of polyoxyethylene glycerol ether and stir evenly to obtain the modified hydrogenated castor oil.
[0014] By adopting the above technical solution, it is found in the actual application process that the modified hydrogenated castor oil can have a good synergistic effect with ethylene bislauramide, improving the adhesion of lead-free solder paste. However, after the lead-free solder paste is printed, the surface of the solder joints is prone to the problem of coarsening. This may be because the addition of conventional modified hydrogenated castor oil will cause the lead-free solder paste to have the problem of false thickening. Therefore, the modified hydrogenated castor oil is further optimized. The modified hydrogenated castor oil in this application first melts hydrogenated castor oil and maleic anhydride into a liquid, and then under optimal temperature and time conditions, the hydrogenated castor oil and maleic anhydride carry out an esterification reaction, introducing a maleic anhydride structure into the molecular chain segment of hydrogenated castor oil. Then, it is mixed and compounded with cyclohexane-1,2-dicarboxylic acid diglycidyl ester and polyoxyethylene glycerol ether. The molecular chain segments of hydrogenated castor oil that can be esterified with maleic anhydride are intertwined with each other, further enhancing the wettability and viscosity stability of the prepared modified hydrogenated castor oil, improving the dispersion uniformity and stability of solder powder in the flux, making the lead-free solder paste not prone to false thickening and coarsening problems, and thus enhancing the connection strength and stability of the lead-free solder paste.
[0015] Preferably, the organic acid activator is at least two combinations of citric acid, malic acid, succinic acid, butanedioic acid, dipropionic acid, and decyltetradecanoic acid.
[0016] By adopting the above technical solution, the above organic acid activator can enhance the activity and stability of the flux, improve the wettability and the ability to remove oxides of lead-free solder paste during the soldering process, and at the same time will not corrode the PCB board, improving the quality and connection strength of soldered joints.
[0017] Preferably, the surfactant is at least one of oleyl polyoxyethylene ether, fluorosurfactant, Triton X-100, and polyethylene glycol 400 - 1000.
[0018] By adopting the above technical solutions, the above surfactant can effectively improve the wettability and dispersibility of the flux, enhance the degree of uniform mixing between the solder powder and the flux, and further improve the spreading performance of the lead-free solder paste on the PCB board, thereby enhancing the connection strength of the soldered joints and reducing problems such as false soldering caused by poor wetting.
[0019] Preferably, the solvent is at least a combination of two of triisopropanolamine, diethylene glycol monohexyl ether, propylene glycol methyl ether, diethylene glycol dibutyl ether, tetrahydrofurfuryl alcohol, and tetraethylene glycol; the antioxidant is 1-hydroxybenzotriazole and / or phosphate ester.
[0020] By adopting the above technical solutions, the above solvent can effectively adjust the viscosity and fluidity of the flux, ensuring good coating performance during the soldering process. The addition of the antioxidant significantly improves the antioxidant ability of the lead-free solder paste, reducing the occurrence of oxidation reactions during long-term storage and use, thereby enhancing the stability and reliability of the solder joints.
[0021] In a second aspect, the present application provides a method for preparing a lead-free solder paste with high connection strength, adopting the following technical solutions: A method for preparing a lead-free solder paste with high connection strength includes the following preparation steps: S1. Add rosin auxiliary agent, organic acid activator, thixotropic agent, surfactant, solvent, and antioxidant into an emulsifying device for emulsification, and then use a grinding device for grinding to obtain the flux. S2. Stir and disperse the solder powder and the flux to obtain a lead-free solder paste with high connection strength.
[0022] By adopting the above technical solutions, the components in the flux are fully emulsified and ground to improve the system dispersion uniformity of the flux. Then, the solder powder and the flux are fully stirred and dispersed. This preparation process is simple and easy to operate, and can effectively enhance the stability of the prepared lead-free solder paste.
[0023] Preferably, the emulsification temperature in step S1 is 80 - 100 °C, and the emulsification time is 6 - 10 h.
[0024] By adopting the above technical solutions, by optimizing the emulsification temperature and time, it promotes the full dissolution and mixing of each component to form a stable emulsification system, which can effectively improve the uniformity and stability of each component in the flux.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The lead-free solder paste of the present application uses polymerized rosin, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol as rosin auxiliaries, modified hydrogenated castor oil and ethylene bislauramide as thixotropic agents, and compounded organic acid activators, surfactants, antioxidants, and solvents to prepare a soldering flux, which can effectively remove the oxide film and contaminants on the PCB board and chip pins, improve the fluidity and wettability of the prepared lead-free solder paste, and at the same time improve the adhesion retention and thermal collapse properties. It can be applied to fine chip packaging. In a complex working environment, especially during the frequent thermal expansion and contraction process and frequent vibration process of the chip, there are also no problems of wet and broken soldering points.
[0026] 2. Using polymerized rosin 115, polymerized rosin 140, and dimerized rosin in a preferred ratio as the polymerized rosin, the three have a good synergistic effect, can have good adhesion while having a good softening point and fluidity, and effectively reduce the stress concentration problem at the soldering points during the soldering process.
[0027] 3. Using modified hydrogenated castor oil and ethylene bislauramide in a preferred weight ratio as thixotropic agents, and by melting hydrogenated castor oil and maleic anhydride and carrying out an esterification reaction to introduce a maleic anhydride structure into the molecular chain segment of hydrogenated castor oil, and then mixing and compounding with cyclohexane-1,2-dicarboxylic acid diglycidyl ester and polyoxyethylene glycerol ether to prepare modified hydrogenated castor oil, so that the prepared lead-free solder paste is not prone to false thickening and coarsening problems, thereby improving the connection strength and stability of the lead-free solder paste. Detailed Embodiments
[0028] The following further details the present application in conjunction with embodiments.
[0029] The following are the sources and specifications of some raw materials of the present application. The raw materials used in the preparation examples and embodiments of the present application can all be obtained commercially, including but not limited to the raw materials of the following models and manufacturers, and raw materials with the same performance can all be used: 1. Pentaerythritol ester of hydrogenated rosin: CAS No. 64365-17-9, content 99%; 2. Hydrogenated rosin alcohol: ABITOL-E, CAS No. 13393-93-6, content 99%; 3. Ethylene bislauramide: EBL, melting point 145-155 °C; 4. Polymerized rosin 115: Yoshida Chemical Industry, softening point 110-120 °C, content 99%; 5. Polymerized rosin 140: Yoshida Chemical Industry, model AJ04, softening point 135-145 °C; 6. Dimerized rosin: DMER-145, softening point 140-150 °C; 7. Diglycidyl cyclohexane-1,2-dicarboxylate: CAS No. 5493-45-8, content 99%; 8. Polyoxyethylene glycerol ether: MF-200A; 9. Maleic anhydride: CAS No. 108-31-6, content 99%; 10. Hydrogenated castor oil: CAS No. 8001-78-3, content 99%; 11. Solder powder: 305 tin-silver-copper alloy powder, tin 96.5 wt% / silver 3.0 wt% / copper 0.5 wt%, particle size 20 - 38 μm.
[0030] Preparation example of modified hydrogenated castor oil Preparation example 1 Preparation example 1 discloses a modified hydrogenated castor oil, which is prepared by the following steps: Add 4 kg of hydrogenated castor oil and 0.5 kg of maleic anhydride to a reaction kettle, heat up to 90 °C, react for 3 h after melting, then add 0.4 kg of diglycidyl cyclohexane-1,2-dicarboxylate and 0.5 kg of polyoxyethylene glycerol ether and stir evenly to obtain the modified hydrogenated castor oil.
[0031] Preparation examples 2 - 3 The differences between preparation examples 2 - 3 and preparation example 1 are that the raw material dosages and preparation conditions are different. See Table 1 below for details.
[0032] Table 1 Parameter table of preparation examples 1 - 3 Preparation example 4 The difference between preparation example 4 and preparation example 1 is that diglycidyl cyclohexane-1,2-dicarboxylate is replaced with polyoxyethylene glycerol ether in equal amount, and the others are the same as preparation example 1.
[0033] Preparation example 5 The difference between preparation example 5 and preparation example 1 is that polyoxyethylene glycerol ether is replaced with hydrogenated castor oil in equal amount, and the others are the same as preparation example 1.
[0034] Preparation example 6 The difference between preparation example 6 and preparation example 1 is that 4 kg of hydrogenated castor oil and 0.5 kg of maleic anhydride are added to a reaction kettle, heated up to 90 °C, reacted for 3 h after melting to obtain the modified hydrogenated castor oil. Examples
[0035] Example 1 Example 1 discloses a lead-free solder paste with high bonding strength, which is prepared by the following steps: S1. Add 1 kg of rosin auxiliary (composed of polymerized rosin 140, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol with a weight ratio of 3:1:0.2), 1.2 kg of organic acid activator (composed of succinic acid and dimalonic acid with a weight ratio of 2:1), 0.8 kg of thixotropic agent (composed of commercially available modified hydrogenated castor oil and ethylene bislauramide with a weight ratio of 3:1), 0.6 kg of surfactant (composed of Triton X-100 and polyethylene glycol 400 with a weight ratio of 3:1), 5.9 kg of solvent (composed of triisopropanolamine and diethylene glycol monohexyl ether with a weight ratio of 2:1), and 0.5 kg of 1-hydroxybenzotriazole as an antioxidant into an emulsifier for emulsification. The emulsification temperature is 80 °C and the emulsification time is 10 h. Then, use a three-roll mill for grinding to obtain a soldering flux; S2. Stir and disperse 8.8 kg of solder powder and 1.2 kg of soldering flux evenly to obtain a lead-free solder paste with high connection strength; The commercially available modified hydrogenated castor oil is Arkema CRAYVALLAC MT.
[0036] Example 2 - 3 The differences between Example 2 - 3 and Example 1 are that the raw material dosages and preparation parameters are different. For details, see Table 2 below.
[0037] Table 2 Parameter table of Examples 1 - 3 Examples 4 - 9 The differences between Examples 4 - 9 and Example 1 are that the sources of the modified hydrogenated castor oil are different. For details, see Table 3 below.
[0038] Table 3 Source table of the modified hydrogenated castor oil in Examples 4 - 9 Example Source of Modified Hydrogenated Castor Oil Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Example 4 Example 8 Preparation Example 5 Example 9 Preparation Example 6 Example 10 The difference between Example 10 and Example 4 is that the polymerized rosin is composed of polymerized rosin 115, polymerized rosin 140, and dimerized rosin with a weight ratio of 1:1:0.3, and the others are the same as Example 4.
[0039] Example 11 The difference between Example 11 and Example 4 is that the polymerized rosin is composed of polymerized rosin 115, polymerized rosin 140, and dimerized rosin with a weight ratio of 1:2:0.6, and the others are the same as Example 4.
[0040] Comparative example Comparative example 1 The difference between Comparative example 1 and Example 1 is that the pentaerythritol ester of hydrogenated rosin is replaced with hydrogenated rosin alcohol in equal amounts, and the others are the same as Example 1.
[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that 140 parts by weight of polymerized rosin is replaced with pentaerythritol ester of hydrogenated rosin in equal amount, and the others are the same as those in Example 1.
[0042] Performance Detection Test The following is the performance test on the high connection strength lead-free solder pastes prepared in Examples 1-11 and Comparative Examples 1-2: 1. Thermal Collapse Test: According to JIS Z 3284 standard, after heating at 200 °C for 120 s, the collapse of the lead-free solder paste (unit: mm) is tested, and the test results are tested and recorded; 2. Adhesion Retention: According to JIS Z 3284 standard, the adhesion of the lead-free solder paste after printing for 24 h (unit: N) is tested, and the test results are tested and recorded; 3. Application Test: (1) The lead-free solder paste is applied to chip packaging, and the solder joints with a diameter of 0.2 mm are controlled for welding to obtain finished products. The finished product boards are alternately placed in an environment at 90 °C and -10 °C for 30 min each time, with an interval of 5 min in between. After 25 times of thermal cycling test, the PCB boards are dropped from a 3 m high platform, and whether there is solder fracture problem in the finished products is detected after the test, and the test results are recorded; (2) The lead-free solder paste is applied to chip packaging, and the solder joints with a diameter of 0.2 mm are controlled for welding to obtain finished products. The finished product boards are placed in an environment at 85 °C and 85% humidity for 72 h, and then the PCB boards are dropped from a 3 m high platform. Whether there is solder fracture problem in the finished products is detected after the test, and the test results are recorded.
[0043] The following are the performance test data of the high connection strength lead-free solder pastes prepared in Examples 1-11 and Comparative Examples 1-2, as shown in Table 4 below for details.
[0044] Table 4 Performance Data Table of Examples 1-11 and Comparative Examples 1-2 Combining Examples 1 - 3 and Examples 4 - 8 and referring to Table 4, it can be concluded that when using the modified hydrogenated castor oil of the present application as a thixotropic agent and compounding it with ethylene bislauramide, the prepared lead-free solder paste has lower thermal collapse, better adhesion retention, and all pass the drop tests after temperature resistance and damp heat resistance tests, showing good connection strength and stability. Compared with Example 4, in Examples 6 - 8, the components of the raw materials for preparing the modified hydrogenated castor oil were changed, resulting in higher thermal collapse and lower adhesion retention of the prepared lead-free solder paste. After the temperature change test, problems such as fracture of the solder part occurred, which may be because the change in the modified hydrogenated castor oil affected the thixotropic properties of the lead-free solder paste, prone to problems such as false thickening and adhesion change, thereby reducing the connection strength and stability of the lead-free solder paste.
[0045] Combining Example 1 and Comparative Examples 1 - 2 and referring to Table 4, it can be concluded that using the polymerized rosin, pentaerythritol ester of hydrogenated rosin, and hydrogenated rosin alcohol of the present application as rosin resins can improve the connection strength and stability of the prepared lead-free solder paste. Further combining Example 4 and Examples 10 - 11, it can be concluded that further optimizing the type and ratio of the polymerized rosin can further improve the connection strength and stability of the prepared lead-free solder paste.
[0046] The lead-free solder paste of the present application can be applied to the fine chip packaging with a solder joint diameter of 0.2 mm, having good connection strength and stability, and is not prone to solder fracture problems.
[0047] This specific embodiment is only an interpretation of the present application and is not a limitation thereto. Those skilled in the art can make modifications without creative contributions to this embodiment as needed after reading this specification, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.
Claims
1. A lead-free solder paste with high connection strength, characterized in that: The invention is made of 88-92wt% solder powder and 8-12wt% soldering flux, wherein the soldering flux comprises 10-20wt% rosin additive, 8-15wt% organic acid activator, 5-8wt% thixotropic agent, 3-6wt% surfactant, 2-5wt% antioxidant and the balance solvent; the rosin additive comprises polymerized rosin, hydrogenated rosin pentaerythritol ester and hydrogenated rosin alcohol; and the thixotropic agent comprises modified hydrogenated castor oil and ethylene bislauramide.
2. The high connection strength lead-free solder paste according to claim 1, characterized in that: The rosin auxiliary agent is composed of polymerized rosin, hydrogenated rosin pentaerythritol ester and hydrogenated rosin alcohol in a weight ratio of 3:(1-2):(0.2-0.5).
3. A lead-free solder paste with high connection strength according to claim 2, characterized in that: The polymerized rosin is composed of polymerized rosin 115, polymerized rosin 140 and dimerized rosin in a weight ratio of 1:(1-2):(0.3-0.6).
4. The high connection strength lead-free solder paste according to claim 1, characterized in that: The thixotropic agent is composed of modified hydrogenated castor oil and ethylene bislauramide in a weight ratio of (3-4):
1.
5. The high connection strength lead-free solder paste according to claim 4, characterized in that: The modified hydrogenated castor oil is prepared by the following steps: by weight, 40-60 parts of hydrogenated castor oil and 5-10 parts of maleic anhydride are added into a reaction device, the temperature is raised to 90-100° C., reacted for 2-3 hours after melting, and then 2-4 parts of cyclohexane-1,2-dicarboxylic acid diglycidyl ester and 5-8 parts of polyoxyethylene glycerol ether are added and stirred evenly to prepare the modified hydrogenated castor oil.
6. The high connection strength lead-free solder paste according to claim 1, characterized in that: The organic acid active agent is a combination of at least two of citric acid, malic acid, succinic acid, succinic acid, dipropionic acid, and decyltetradecanoic acid.
7. The high connection strength lead-free solder paste according to claim 1, characterized in that: The surfactant is at least one of oleyl alcohol polyoxyethylene ether, fluorine surfactant, Triton X-100 and polyethylene glycol 400-1000.
8. The high connection strength lead-free solder paste according to claim 1, characterized in that: The solvent is a combination of at least two of triisopropanolamine, diethylene glycol monohexyl ether, propylene glycol methyl ether, diethylene glycol dibutyl ether, tetrahydrofurfuryl alcohol and tetraethylene glycol; and the antioxidant is 1-hydroxybenzotriazole and / or phosphate.
9. A method for preparing a lead-free solder paste with high connection strength as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1, adding rosin additive, organic acid activator, thixotropic agent, surfactant, solvent and antioxidant into an emulsifying device for emulsification, and then grinding with a grinding device to obtain a soldering flux; S2. Stir and disperse the solder powder and flux to obtain a lead-free solder paste with high connection strength.
10. The method for preparing a lead-free solder paste with high connection strength according to claim 9, characterized in that: The emulsification temperature in step S1 is 80-100° C., and the emulsification time is 6-10 h.
Citation Information
Cited By
Soldering flux, low-voidage high-lead soldering paste and preparation method of soldering flux
CN121267469A